Formation and geological significance of carbonate firmgrounds and hardgrounds on the Rio Grande Rise (South Atlantic) - Alexandre Henrique Ferraz; Rafael Oliveira Silva; Pedro Walfir Martins e Souza Neto; Carina Ulsen; Lucy Gomes Sant'Anna; Paulo César Fonseca Giannini; Eugenio Pires Frazão; Victor Hugo Rocha Lopes; Luigi Jovane; Bramley J. Murton; Christian Millo (Sedimentary Geology, 2026)

Collaborative monitoring networks refine jaguar habitat suitability and reveal conservation gaps in the Brazilian Cerrado - Lucas Gonçalves da Silva; Marco Aurélio Mendes Elias; Juliana Silveira dos Santos; Anah Tereza de Almeida Jácomo; Douglas Santos; Ennio Painkow Neto; Fabio Hudson Souza Soares; Gabriel Caputo de Carvalho; Giselle Bastos Alves; Gonzalo Barquero; Igor Fagundes Perfeito; Marina Motta de Carvalho; et al. (Biological Conservation, 2026)

Productive, physiological, and biochemical responses of elephant grass ‘BRS Capiaçu’ (Pennisetum purpureum Schumach.) under different water regimes with brackish water in a semi-arid environment - Lara Rosa de Lima-Silva; Lady Daiane Costa de Sousa Martins; Alexandre Maniçoba da Rosa Ferraz Jardim; Wagner Martins dos Santos; Pedro Paulo Santos de Souza; Luciana Sandra Bastos de Souza; Cleber Pereira Alves; Agda Raiany Mota dos Santos; Ênio Farias de França e Silva; Hugo Rafael Bentzen Santos; Wilma Roberta dos Santos; Carlos André Alves de Souza; et al. (Physiology and Molecular Biology of Plants, 2026)
The seasonality of forage production is one of the main challenges in semi-arid regions, where environmental conditions limit agricultural productivity. One promising option is the use of elephant grass ‘BRS Capiaçu’, together with deficit irrigation. This study evaluated the impact of different irrigation depths with brackish water (50%, 75%, 100% and 125% of the reference evapotranspiration – ET 0 ) on the productive, physiological, photochemical and biochemical aspects of ‘BRS Capiaçu’ over two cycles. Irrigation with 50% of the ET 0 resulted in lower rates of net photosynthesis (P n ), with a reduction in photosystem II quantum yield (ΔF/Fm’), qP, NPQ and the electron transport rate (ETR), in addition to greater activity of the antioxidant enzymes superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX), indicating oxidative stress. The depths of 50% and 100% of the ET 0 resulted in greater dry matter production, for Cycles 1 and 2, respectively, demonstrating the resilience of the crop to water stress, attributed to such mechanisms of acclimatisation as a reduction in transpiration (T r ) and an increase in water use efficiency. These physiological changes were more obvious during Cycle 2, in which the crop was subjected to lower rainfall (47.8 mm), while salt stress was also more pronounced during this period, in response, the plants showed less water loss through transpiration and larger WUE inst . It was concluded that ‘BRS Capiaçu’ has a high capacity for acclimatisation to semi-arid conditions, and stands out as a viable alternative for mitigating the seasonality of forage production and promoting sustainable livestock farming in the region.

A combination of resilient practices maximizes productivity and water, carbon, and nutrient stocks in forage species systems in the Brazilian semi-arid region - Marcelo José da Silva; Wilma Roberta dos Santos; Cleber Pereira Alves; Alexandre Maniçoba da Rosa Ferraz Jardim; Agda Raiany Mota dos Santos; Álefe Chagas de Lima Costa; Carlos André Alves de Souza; José Edson Florentino de Morais; Luciana Sandra Bastos de Souza; João Pedro Alves de Souza Santos; Ênio Farias de França e Silva; Fleming Sena Campos; et al. (International Journal of Plant Production, 2026)
Adopting resilient practices is crucial to balancing food production and crop sustainability in semiarid regions. Therefore, adopting systems that provide greater stocks of water, carbon, and nutrients at the soil-plant interface is crucial. The objective of this study was to assess water, carbon, and nutrient stocks in the soil-plant systems of irrigated forage crops in the semiarid region of Brazil. The study was conducted in Serra Talhada, Pernambuco, Brazil. Four production cycles were evaluated between January 2017 and January 2022, comprising seven cropping systems: pigeon pea (S1), millet (S2), sorghum (S3), cactus forage (S4), cactus forage-sunflower-pigeon pea (S5), cactus forage-sorghum-millet (S6), and cactus forage-sorghum (S7). The following parameters were evaluated: fresh matter (FM) and dry matter (DM) productivity, as well as water, organic carbon (OC), and nutrient (N, P, K + , Ca 2+ , Mg 2+ , and Na + ) stocks in the plant and soil at depths of 0–20 and 20–40 cm. The intercropping systems presented the highest mean values for each of the plant variables. Among the single systems, forage cactus did not differ from the intercropped systems for FM, plant stocks of P, Ca 2+ , Mg 2+ , and water. The single sorghum presented higher values for plant DM (44.0 Mg ha −1 ) and plant OC (18.7 Mg ha −1 ). For soil variables, only the levels of P, K + , Na +, and OC showed significant differences ( p < 0.05). The single forage cactus had the highest average soil OC value (14.5 Mg ha −1 ). The cactus-sorghum intercrop system appears to offer the best balance between productivity and water, OC, and nutrient reserves. Among the isolated systems, forage cactus stores the largest amounts of OC in the soil, while sorghum stands out for accumulating carbon in the plants. Studies on the sustainability of forage species should be encouraged to improve the development of agricultural systems.

Ecological and social contexts of scorpion stings in Manaus, the largest metropolis of the Brazilian Amazon - Zehev S. Benzaken; Joseir Saturnino Cristino; Haicha Benzaken; Jacqueline Sachett; Erica da Silva Carvalho; Yasmin da Silva Mendes; Handerson da Silva Pereira; Alexandre Silva-Neto; Fan Hui Wen; Maria das Graças Vale Barbosa Guerra; Wuelton Monteiro (Toxicon, 2026)

Protocol for Defining the Agricultural Calendar and Yield Gap Using the AquaCrop Model: A Case Study for Sorghum Under High‐Salinity Water Irrigation in Current and Future Climate Conditions in Pernambuco, Brazil - Cleber Pereira Alves; Danielle da Silva Eugenio; Kaique Renan da Silva Salvador; Agda Raiany Mota dos Santos; Carlos André Alves de Souza; Alexandre Maniçoba da Rosa Ferraz Jardim; João Emanoel Ambrósio Gomes; Antonio José Steidle Neto; Luciana Sandra Bastos de Souza; Elania Freire da Silva; Magna Soelma Beserra de Moura; Fleming Sena Campos; et al. (Irrigation and Drainage, 2026)
In the face of climate change, agricultural modelling combined with experimental research is essential for predicting yields in diverse climatic scenarios. This study calibrated, validated and applied the AquaCrop model for forage sorghum under future climate scenarios in a semi‐arid region between 2020 and 2022. Meteorological data, soil moisture, canopy cover and crop productivity were collected. Model performance was evaluated using: Pearson's correlation coefficient, Willmott's index of agreement, confidence index, coefficient of determination, root mean square error, normalised RMSE, mean bias error and the Nash–Sutcliffe model efficiency coefficient. After calibration, simulations were performed for 11 semi‐arid locations to estimate yield gaps, optimal sowing periods and future projections (2030–2100). Future climate data were obtained from the CanESM2 model under the RCP 4.5 scenario and adjusted for bias correction based on historical observations (1961–2020). AquaCrop demonstrated strong predictive accuracy for productivity and canopy cover. Under the RCP 4.5 scenario, increased rainfall during the growing season resulted in an approximately 35% increase in achievable productivity. Yield gaps were more affected by management practices than by water deficit, averaging 42%. Overall, AquaCrop has proven to be an effective tool for defining agricultural calendars and supporting water management strategies in diverse environmental conditions.

Chemical analysis and biological activity of crude extracts obtained from leaves of Passiflora foetida (Subg. Passiflora ) and Passiflora morifolia (Subg. Decaloba) - Ohana Luiza Santos de Oliveira; Oscar Caetano da Silva Neto; Gabriele Rodrigues Conceição; Fábio Alexandre Chinalia; Daniel Pereira Bezerra; Milena Botelho Pereira Soares; Valdenizia Rodrigues Silva; Luciano de Souza Santos; Carla Junqueira Moragas Tellís; João Victor da Silva e Silva; Caroline Conceição da Guarda; Jorge Mauricio David; et al. (Natural Product Research, 2026)

Analysis of the physical and chemical characteristics of stored and fresh Leucaena leucocephala seeds - Viviane da Silva Sousa Almeida; Amanda Graziela Gonçalves Mendes; Tonicley Alexandre da Silva; Daniele Gomes Cassias Rodrigues; Ariadina Jansen Campos Fontes; José Lima Pereira-Filho; Carmem Duarte Lima Campos; Aleania Polassa Almeida Pereira; João Lucas do Carmo Lima; Kátia Danielle Araújo Lourenço Viana; Valério Monteiro-Neto (Food Research International, 2026)

Cultivar-dependent soil microbial responses to contrasting nitrogen management strategies in Cenchrus purpureus systems with and without Clitoria ternatea - Dayanne Camelo; Márcio Vieira da Cunha; José Carlos Batista Dubeux; Giselle Gomes Monteiro Fracetto; Mércia Virgínia Ferreira dos Santos; Valdson José da Silva; Alexandre Carneiro Leão de Mello; Brenda Vergetti Albuquerque Botelho; Djalma Euzébio Simões Neto (Plant and Soil, 2026)
Background and aims In grass-based forage systems, integrating legumes can stimulate soil microbial communities, strengthen biogeochemical cycling, and reduce reliance on synthetic nitrogen inputs. However, soil responses may vary according to the grass cultivar. Cenchrus purpureus (Schumach.) Morrone cultivars contrasting in plant height, Mercker (tall) and Mott (dwarf), were evaluated under nitrogen-fertilised monoculture (300 kg N ha⁻ 1 yr⁻ 1 ) and intercropping with Clitoria ternatea L. without mineral nitrogen input, representing contrasting nitrogen management strategies. Methods Soil organic matter fractions, glomalin-related soil proteins, microbial biomass carbon and nitrogen, soil basal respiration, and microbial efficiency indices were assessed across seasons at 0–10, 10–20, and 20–40 cm soil depths using a randomised complete block design with four replications. Results Intercropping did not affect recalcitrant carbon pools (humic acid and humin) but increased fulvic acid carbon, particularly in Mercker-based systems. Seasonal variation exerted stronger control over humic and glomalin fractions than the cropping system. Mott + C. ternatea was associated with lower microbial biomass carbon, whereas basal respiration was not affected by cropping system. Mercker-based systems showed patterns potentially associated with greater microbial efficiency, whereas Mott + C. ternatea intercropping exhibited higher qCO₂ and more variable responses of qMIC and qMin across seasons and soil depths. Conclusions Greater belowground complementarity between the tall Mercker cultivar and C. ternatea was associated with patterns consistent with improved microbial metabolic efficiency indicators, suggesting potential effects on carbon stabilisation and microbially mediated nutrient cycling and highlighting the cultivar dependence of legume-based nitrogen supply in C. purpureus cut-and-carry systems.

Long-term crop diversity improves soil chemical attributes, nutrient cycling and soybean yield - Andressa Selestina Dalla Côrt; Leandro Pereira Pacheco; Bruno Moço Tessarolli; Eder Rodrigues Batista; Isabô Melina Pascoalotto; João William Bossolani; Evelyn Custódio Gonçalves; Kamila Silva de Macedo; Thaís Rodrigues Magalhães Guedes; Vinícius Hipólito Lopes de Resende; Fabiano André Petter; Edicarlos Damacena de Souza; et al. (Nutrient Cycling in Agroecosystems, 2026)
Cover crops have the potential to reduce agricultural inputs, but the long-term impacts of cover crops on soil chemical properties and nutrient cycling in tropical systems are not fully understood. This study evaluated the impact of different cover crop systems under long-term no-tillage on shoot dry mass (SDM) production, nutrient cycling, soil chemical properties, and soybean yield in succession in the Cerrado region of Mato Grosso State, Brazil. The treatments consisted of different second crops after soybean cultivation: MC (soybean monocropped), fallow; CS1, Crotalaria spectabilis ; CS2, Pennisetum glaucum ; CS3, Urochloa ruziziensis ; CS4, Cajanus cajan ; and MIX, C. spectabilis + P. glaucum + U. ruziziensis + C. cajan . SDM was evaluated at 0, 90, 105, 120, 150, 180, and 210 days after chemical desiccation of the cover crop using herbicides in the crop years from 2014/15 to 2020/21. Soil chemical properties were evaluated after the 2019/20 soybean harvest. MIX increased SDM by approximately 22% compared with CS2 and CS3 and 60% compared with MC. In years 6 and 7, soybean yields were significantly higher in MIX, CS3, and CS4 than in MC, increasing by approximately 840 kg ha −1 . MIX resulted in the greatest long-term improvements in soil cation exchange capacity, pH, nutrient release and concentration, organic matter, and soybean yield. Even when grown individually, U. ruziziensis , C. cajan , and C. spectabilis also had positive effects on these parameters. Thus, crop successions with cover crops promote improvements in soil fertility and are a sustainable long-term strategy to enhance soybean productivity in the Brazilian Cerrado.

Intensified tropical pasture-based beef cattle production systems and their effects on carcass traits, meat quality and methane emissions from Nellore steers - Gabriele Voltareli da Silva; Rolando Pasquini Neto; Mariana Nunes Vieira de Melo; Luiza Budasz de Andrade; Althieres José Furtado; Ester Costa Fabricio; Analisa Vasques Bertoloni; Annelise Aila Gomes Lobo; Flavio Perna Junior; Sérgio Raposo de Medeiros; Alexandre Berndt; Renata Tieko Nassu; et al. (Livestock Science, 2026)

Management Strategies and Agricultural Calendars for Forage Production in Semi‐Arid Brazil Using AquaCrop - Antonio Gebson Pinheiro; Cleber Pereira Alves; Carlos André Alves de Souza; George do Nascimento Araújo Júnior; Alexandre Maniçoba da Rosa Ferraz Jardim; Regina Crisóstomo Grangeiro Pereira; José Edson Florentino de Morais; Luciana Sandra Bastos de Souza; Daniela de Carvalho Lopes; Antonio José Steidle Neto; Adriano Nascimento Simões; Fleming Sena Campos; et al. (Irrigation and Drainage, 2026)
Forage production in semi‐arid regions of Brazil is limited by water deficit. This study aimed to identify the most adapted and efficient production systems and define their agricultural calendars for the semi‐arid region of Brazil. Twenty‐nine production arrangements that included different cropping conditions, plant density, plant cycles, water replenishment, use of soil cover and production arrangements based on the main crop (forage cactus) were simulated for 14 locations. On the basis of the agricultural calendar, planning from the beginning of December to January is ideal for rainfed systems. Compared with their monoculture systems, the intercropping system of forage cactus and irrigated sorghum increased the forage supply by 44% and 89%, respectively. The use of irrigation increased the forage cactus biomass by 150%, with an emphasis on the clone Orelha de Elefante Mexicana, which presented an average water productivity of 39 g m −2 . The increase in the planting density of the forage cactus increased productivity by up to 140% under the control. The use of irrigated forage cactus and sorghum intercropping should be recommended, in addition to practices such as higher planting densities and the use of mulch to optimise yield.

First report of Penicillium digitatum causing postharvest rot in lemon in Brazil - Glícia Silva de Moraes; Amanda Cupertino de Queiroz Brito; Ana Elisa de Almeida Souza; Jordana Alves da Silva Melo; José Vitorino da Silva Neto; Cristina Maria de Souza-Motta; Alexandre Reis Machado (Journal of Plant Pathology, 2026)

Satellite evidence for persistent degradation in Brazil's desertification nuclei - Alanderson Firmino de Lucas; Marcos Vinícius da Silva; Alexandre Maniçoba da Rosa Ferraz Jardim; Luciana Sandra Bastos de Souza; Gabriel Thales Barboza Marinho; Lady Daiane Costa de Sousa Martins; João Emanoel Ambrósio Gomes; Gledson Luiz Pontes de Almeida; Jhon Lennon Bezerra da Silva; Wilma Roberta dos Santos; Wagner Martins dos Santos; Elania Freire da Silva; et al. (Remote Sensing Applications: Society and Environment, 2026)

Proof of concept of a wearable IoT-based system for monitoring respiratory rate and surface temperature in horses - Brendo Junior Pereira Farias; Dermeval Araújo Furtado; José Wallace Barbosa do Nascimento; José Pinheiro Lopes Neto; Fabiana Terezinha Leal de Morais; Thiago Lira Souza Santos; Alexandre Sales Vasconcelos; Rafael Costa Silva; José Ilton Pereira Alves; Concepta Mcmanus; Robson Mateus Freitas Silveira; Neila Lidiany Ribeiro (Journal of Equine Veterinary Science, 2025)

Rainfall partitioning of tree species in a seasonally dry forest in a semiarid region of Brazil - Carlos André Alves de Souza; Alexandre Maniçoba da Rosa Ferraz Jardim; Luciana Sandra Bastos de Souza; José Edson Florentino de Morais; George do Nascimento Araújo Júnior; Cleber Pereira Alves; Daniela Carvalho Lopes; Antonio José Steidle Neto; Gabriel Ítalo Novaes da Silva; Wilma Roberta dos Santos; Elisiane Alba; Ênio Farias de França e Silva; et al. (Ecohydrology & Hydrobiology, 2025)

Agronomic Performance and Water Use Indicators of Cactus Species Widely Cultivated in Semiarid Regions - George do Nascimento Araújo Júnior; Luciana Sandra Bastos de Souza; Alexandre Maniçoba da Rosa Ferraz Jardim; Carlos André Alves de Souza; Sérvulo Mercier Siqueira e Silva; Djalma Cordeiro dos Santos; Antonio José Steidle Neto; José Edson Florentino de Morais; José Francisco da Cruz Neto; Marcelo José da Silva; José Carlos Mendonça; Enio Farias de França e Silva; et al. (Irrigation and Drainage, 2025)
This study aimed to evaluate the agronomic performance, crop evapotranspiration (ET c ), crop coefficients (K c , K cb and K e ) and yield response factor (K y ) of three forage cactus clones—Orelha de Elefante Mexicana (OEM), Miúda (MIU) and IPA Sertânia (IPA)—grown in a semiarid environment. Four experiments involving different irrigation strategies and the use of mulch were conducted between 2012 and 2020. The OEM clone presented the highest yields of fresh matter (428.44 Mg ha −1 ) and dry matter (39.14 Mg ha −1 ). The use of mulch increased the average productivity by 15% and reduced soil evaporation by 13%. The highest ET c (3.14 mm day −1 ) was recorded for the OEM. The average K c values under cultivation without mulch were 0.61 (OEM), 0.59 (MIU) and 0.62 (IPA). When cultivated with mulch (8.2 Mg ha −1 ), a K c value of 0.45 (OEM) was observed. Under a relatively high mulch rate (18 Mg ha −1 ), the K c values increased to 0.70 (OEM), 0.66 (MIU) and 0.63 (IPA). The average K y across clones was 0.80, reinforcing the adaptability of the forage cactus to the semiarid region. The results highlight the influence of species and management strategies on water use and productivity, emphasizing the importance of considering these factors in irrigation planning.

Pomegranates, pesticides and our heart - Fulvio Alexandre Scorza; Raphael Wuo-Silva; Josef Finsterer; Feres Chaddad-Neto (Food and Chemical Toxicology, 2025)

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Validation of a desertification monitoring model in a semiarid region with the support of machine learning techniques - José Francisco da Cruz Neto; Francisco Charles dos Santos Silva; Carlos André Alves de Souza; Alexandre Maniçoba da Rosa Ferraz Jardim; Wilma Roberta dos Santos; Lady Daiane Costa de Sousa Martins; Wagner Martins dos Santos; Alan Mario Zuffo; Thieres George Freire da Silva (Journal of South American Earth Sciences, 2025)

The legacy and future of multiple anthropogenic stressors: Organohalogen compounds in the vulnerable Guiana dolphin (Sotalia guianensis) - Nara de Oliveira-Ferreira; Elitieri B. Santos-Neto; Bárbara M.R. Manhães; Monizze Vannuci-Silva; Adriana Castaldo Colosio; Hernani Gomes da Cunha Ramos; Ian Augusto Gusman Cunha; Lupércio Araújo Barbosa; Ana Paula Cazerta Farro; Drienne Messa Faria; Haydée A. Cunha; Tatiana L. Bisi; et al. (Journal of Hazardous Materials, 2025)

Forage cactus clones suggested for cultivation in arid areas of the world: agronomic performance and water requirement by phenophase - George do Nascimento Araújo Junior; Luciana Sandra Bastos de Souza; Alexandre Maniçoba da Rosa Ferraz Jardim; Carlos André Alves de Souza; Cleber Pereira Alves; Maria da Conceição Silva; Erinaldo Viana de Freitas; Antonio José Steidle Neto; Orivaldo Brunini; José Edson Florentino de Morais; José Francisco da Cruz Neto; Thieres George Freire da Silva (Irrigation Science, 2025)

Energy balance and evapotranspiration conditioned by deforestation of a seasonally dry tropical forest (Caatinga): A series of four water seasons - Thieres George Freire da Silva; Maria Gabriela de Queiroz; Sérgio Zolnier; Alexandre Maniçoba da Rosa Ferraz Jardim; Wilma Roberta dos Santos; Magna Soelma Beserra de Moura; Carlos André Alves de Souza; Antonio José Steidle Neto; George do Nascimento Araújo Júnior; Marcelo José da Silva; Kaique Renan da Silva Salvador; Elania Freire da Silva; et al. (Journal of South American Earth Sciences, 2025)

Performance and feed intake of Nellore steers in extensive, intensive, and integrated pasture-based beef cattle production systems - Rolando Pasquini Neto; Althieres José Furtado; Gabriele Voltareli da Silva; Annelise Aila Gomes Lobo; Adibe Luiz Abdalla Filho; Flavio Perna Junior; Alexandre Berndt; Sérgio Raposo de Medeiros; André de Faria Pedroso; Patrícia Perondi Anchão de Oliveira; Paulo Henrique Mazza Rodrigues (Livestock Science, 2025)

Soil Fertility, Physiological Traits, and Fruit Quality of Morinda citrifolia as Influenced by Agroecological Management Practices in a Tropical Ferralsol - Aline Cavalcanti Dantas; Tancredo Augusto Feitosa de Souza; Thiago Nascimento Coaracy; Belísia Lucia Moreira Toscano Diniz; Emmanuel Moreira Pereira; Manoel Alexandre Diniz Neto; Zenaide Gomes da Silva; Larissa Nicássio Pessoa (Agricultural Research, 2025)

Calibration and validation of the AquaCrop model for forage cactus production systems under different management interventions in the semi-arid region of Brazil - Sidney Anderson Teixeira da Costa; Luciana Sandra Bastos de Souza; Abelardo Antônio de Assunção Montenegro; Carlos André Alves de Souza; José Edson Florentino de Morais; Daniela de Carvalho Lopes; Antonio José Steidle Neto; João Pedro Alves de Souza Santos; Alexandre Maniçoba da Rosa Ferraz Jardim; Cleber Pereira Alves; Marcos Vinícius da Silva; Thieres George Freire da Silva (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Geostatistical modeling of the rainfall patterns and monthly multiscale characterization of drought in the South Coast of the Northeast Brazilian via Standardized Precipitation Index - Marcos Vinícius da Silva; Jhon Lennon Bezerra da Silva; Maria Beatriz Ferreira; Lizandra de Barros de Sousa; Abelardo Antônio de Assunção Montenegro; Jorge Manuel Guieiro Pereira Isidoro; Héliton Pandorfi; José Francisco de Oliveira-Júnior; Helena Maria Neto Paixão Vazquez Fernandez; Fernando Miguel Granja-Martins; Alexandre Maniçoba da Rosa Ferraz Jardim; Thieres George Freire da Silva; et al. (Atmospheric Research, 2024)

Comparison of α and β-acid isomerization in hops and beer using HPLC, confocal microscopy, spectrofluorimetry and chemical analysis of metabolites and essential oils in flowers of different hop cultivars produced in Brazil - Francisco Mateus Gomes do Nascimento; Maria Teresa Salles Trevisan; Manoel Lourenço Alves Neto; Robert Wyn Owen; Edy Sousa de Brito; Lorena Mara Alexandre e Silva; Késya Amanda Dantas Rocha; Carlos Lenz Cesar; Hernandes Faustino de Carvalho; Vitor Bianchin Pelegati; Sthefanny Alves da Silva; Samuel Pedro Dantas Marques (Food Chemistry, 2024)

Insights of potential trypanocidal effect of the synthetic derivative (2E)-1-(4-aminophenyl)-3-(2,4-dichlorophenyl)prop-2-en-1-one: in vitro assay, MEV analysis, quantum study, molecular docking, molecular dynamics, MPO analysis, and predictive ADMET - Márcia Machado Marinho; Matheus Nunes da Rocha; Emanuel Paula Magalhães; Lyanna Rodrigues Ribeiro; Caio Henrique Alexandre Roberto; Francisco Wagner de Queiroz Almeida-Neto; Marília Lopes Monteiro; João Victor Serra Nunes; Ramon Róseo Paula Pessoa Bezerra de Menezes; Emmanuel Silva Marinho; Pedro de Lima Neto; Alice Maria Costa Martins; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Assessment of body metrics, weight, and carcass yields in dusky grouper (Epinephelus marginatus) through correlation and path analysis: Implications for optimizing genetic breeding programs - Graziela Tarôco; Caio Augusto Perazza; Maria Emília de Souza Gomes; Claudia Ehlers Kerber; Rafael Vilhena Reis-Neto; Alexandre Wagner Silva Hilsdorf (Aquaculture, 2024)

Integrating Health and Climate Data to Enhance Snakebite Envenomation Response - Joao Vitor Perez de Souza; Alexandre Vilhena da Silva Neto; Marcos Adriano Garcia Campos; Elle Strand; Wuelton Monteiro; Felipe Murta; Jacqueline Sachett; Fan Wen Hui; Brian McAdoo; Charles Gerardo; Joao Ricardo Nickenig Vissoci (Toxicon, 2024)

Do different densities and planting orientations of forage cactus alter agronomic, morphophysiological characteristics, and soil water dynamics in a semiarid region? - Gabriel Italo Novaes da Silva; José Edson Florentino de Morais; Carlos André Alves de Souza; Alexandre Maniçoba da Rosa Ferraz Jardim; Cléber Pereira Alves; Kaique Renan da Silva Salvador; Luciana Sandra Bastos de Souza; Adriano do Nascimento Simões; Fleming Sena Campos; Antonio José Steidle Neto; Ana Virgínia Marinho Silveira; Abelardo Antônio de Assunção Montenegro; et al. (European Journal of Agronomy, 2024)

Urbanization and scorpion stings in Manaus, the largest metropolis in the Brazilian Amazon - Zehev Benzaken; Lincoln Luís Silva; Alexandre Silva-Neto; Jacqueline Sachett; Nelson Fé; Maria das Graças Vale Barbosa Guerra; Wuelton Monteiro (Toxicon, 2024)

Methyl jasmonate mitigates salt stress and increases quality of purple basil (Ocimum basilicum L.) - Adriano Salviano Lopes; Thiago Jardelino Dias; Juliane Maciel Henschel; Toshik Iarley da Silva; Vitória Stefany de Moura; Agnne Mayara Oliveira Silva; João Everthon da Silva Ribeiro; Manoel Alexandre Diniz Neto; Adailton Bernardo de Oliveira; Diego Silva Batista (South African Journal of Botany, 2024)

Does Covid-19 influence the dynamics of envenomation by animals in a country strongly affected by both conditions? Epidemiological data from Brazil - Pedro Ferreira Bisneto; Alexandre Vilhena da Silva Neto; Jady Shayenne Mota Cordeiro; Wuelton Marcelo Monteiro; Jacqueline de Almeida Gonçalves Sachett (Toxicon, 2024)

Carbon and nitrogen, humic and labile fractions in soil under clonal eucalyptus stands from cerrado - Wendel dos Santos Moraes; Luiz Fernandes Silva Dionisio; Gustavo Schwartz; Juliana Andrade Pereira; Jossimara Ferreira Damascena; Felipe Alexandre Rizzo; Alberto Bentes Brasil Neto; Camila de Almeida Milhomem; José Maria Arcanjo Alves; Renisson Neponuceno Araujo Filho; Renato de Almeida Sarmento; Alinne da Silva; et al. (European Journal of Forest Research, 2024)

Mercury Concentrations in Two Populations of the most Endangered Dolphin (Pontoporia blainvillei) from the Southwestern Atlantic Ocean - Emi Brinatti Guari; Monizze Vannuci-Silva; Bárbara M. R. Manhães; Eduardo Resende Secchi; Silvina Botta; Carolina Pacheco Bertozzi; Elitieri Batista Santos-Neto; Carolina Pereira Dias; Alexandre de Freitas Azevedo; Tatiana Lemos Bisi; Haydée Andrade Cunha; José Lailson-Brito (Bulletin of Environmental Contamination and Toxicology, 2024)

Shifts in microbiota and gene expression of nutrient transporters, mucin and interleukins in the gut of fast-growing and slow-growing chickens infected by Salmonella Enteritidis - Maylane Rayane Brito dos Santos; Alexandre Lemos de Barros Moreira Filho; Oliveiro Caetano Freitas Neto; Maria de Fátima de Souza Andrade; Núbia Michelle Vieira da Silva; Gustavo Felipe Correia Sales; Celso José Bruno de Oliveira; Patrícia Emília Naves Givisiez (Brazilian Journal of Microbiology, 2024)

Intercropping impacts growth in the forage cactus, but complementarity affords greater productivity, competitive ability, biological efficiency and economic return - Kaique Renan da Silva Salvador; Alexandre Maniçoba da Rosa Ferraz Jardim; Cleber Pereira Alves; George do Nascimento Araújo Júnior; Marcelo José da Silva; Leonardo Francelino de Souza; Mário Adriano Ávila Queiroz; Fleming Sena Campos; Glayciane Costa Gois; José Geraldo Eugênio de França; José Nunes Filho; Antonio José Steidle Neto; et al. (Agricultural Systems, 2024)

Capacity of community health centers to treat snakebite envenoming in indigenous territories of the Brazilian Amazon - André Sachett; Eleanor Strand; Thiago Serrão-Pinto; Alexandre da Silva Neto; Thais Pinto Nascimento; Sewbert Rodrigues Jati; Gisele dos Santos Rocha; Sediel Ambrósio Andrade; Fan Hui Wen; Manuela Berto Pucca; João Vissoci; Charles J. Gerardo; et al. (Toxicon, 2024)

Genetic parameters for host-response to acanthocephaliasis caused by the endoparasite Neoechinorhynchus buttnerae in the Amazon fish Colossoma macropomum - John F.G. Agudelo; Baltasar F.G. Neto; Vito A. Mastrochirico-Filho; Raquel B. Ariede; Luis F.S. Moreira; Leilane da Silva Noronha; José M. Yáñez; Alexandre Honczaryk; Gustavo M.R. Valladão; Diogo T. Hashimoto (Aquaculture, 2024)

Calibration and validation of the AquaCrop model for production arrangements of forage cactus and grass in a semi-arid environment - Antonio Gebson Pinheiro; Cleber Pereira Alves; Carlos André Alves de Souza; George do Nascimento Araújo Júnior; Alexandre Maniçoba da Rosa Ferraz Jardim; José Edson Florentino de Morais; Luciana Sandra Bastos de Souza; Daniela de Carvalho Lopes; Antonio José Steidle Neto; Abelardo Antonio de Assunção Montenegro; João Emanoel Ambrósio Gomes; Thieres George Freire da Silva (Ecological Modelling, 2024)

New reports of Gilbertella persicaria causing post-harvest rot in different fruits in Brazil - Ana Elisa de Almeida Souza; André Luiz Cabral Monteiro de Azevedo Santiago; Amanda Cupertino de Queiroz Brito; Juliana Ferreira de Mello; José Vitorino da Silva Neto; Cristina Maria de Souza-Motta; Alexandre Reis Machado (Journal of Plant Diseases and Protection, 2024)

Use of intercropping and mulch to improve the water and natural resources use efficiencies of forage cactus and millet production in a semiarid region - George do Nascimento Araújo Júnior; José Edson Florentino de Morais; Antonio José Steidle Neto; Luciana Sandra Bastos de Souza; Cleber Pereira Alves; Gabriel Ítalo Novaes da Silva; Renan Matheus Cordeiro Leite; Marcelo José da Silva; Alexandre Maniçoba da Rosa Ferraz Jardim; Abelardo Antônio de Assunção Montenegro; Thieres George Freire da Silva (Field Crops Research, 2023)

Africanized honeybee (Apis mellifera) semen freezing using Tris-based and Collins extenders - Lucas da Silva Morais; Edgar Rodrigues de Araujo Neto; Andreia Maria da Silva; Luana Grasiele Pereira Bezerra; Ana Flávia Santos da Cunha; Nailton Oliveira de Sousa Chagas; Romário Parente dos Santos; Genevile Carife Bergamo; Débora Andrea Evangelista Façanha; Katia Peres Gramacho; Alexandre Rodrigues Silva (Tropical Animal Health and Production, 2023)

Intercomparison of micrometeorological variables, surface energy fluxes, and evapotranspiration in different landscapes of the Brazilian semi-arid region - Carlos André Alves de Souza; Alexandre Maniçoba da Rosa Ferraz Jardim; Luciana Sandra Bastos de Souza; George do Nascimento Araújo Júnior; Cleber Pereira Alves; José Edson Florentino de Morais; Daniela de Carvalho Lopes; Antonio José Steidle Neto; Kaique Renan da Silva Salvador; Thieres George Freire da Silva (Agricultural and Forest Meteorology, 2023)

Myrtle (Eugenia gracillima Kiaersk.) as a fermented alcoholic beverage alternative to wine: Preliminary study - Bruno Fonsêca Feitosa; Regilane Marques Feitosa; Emanuel Neto Alves de Oliveira; Rossana Maria Feitosa de Figueirêdo; Alexandre José de Melo Queiroz; Renato Costa da Silva; Inacia dos Santos Moreira; Natiele Piovesan (Food Bioscience, 2023)

Metastatic Sertoli cell tumour in a captive giant anteater (Myrmecophaga tridactyla) - Clarissa H. Santana; Lucas dos R. de Souza; Laice A. da Silva; Ayisa R. Oliveira; Nayara F. de Paula; Daniel O. dos Santos; Fernanda M.A.M. Pereira; André D. Vieira; Letícia N. Ribeiro; Lauro L. Soares-Neto; Alexandre L. da Costa Bicudo; Alícia G. Hippolito; et al. (Journal of Comparative Pathology, 2023)

A systematic review of energy and mass fluxes, and biogeochemical processes in seasonally dry tropical forests and cactus ecosystems - Alexandre Maniçoba da Rosa Ferraz Jardim; José Edson Florentino de Morais; Luciana Sandra Bastos de Souza; Daniela de Carvalho Lopes; Marcos Vinícius da Silva; Héliton Pandorfi; José Francisco de Oliveira-Júnior; Jhon Lennon Bezerra da Silva; Antonio José Steidle Neto; Leonor Patricia Cerdeira Morellato; João L.M.P. de Lima; Thieres George Freire da Silva (Journal of South American Earth Sciences, 2023)

Carvacrol-loaded nanoemulsions produced with a natural emulsifier for lettuce sanitization - Louise Thomé Cardoso; Bibiana Alexandre; Fabiola Ayres Cacciatore; Yve Verônica da Silva Magedans; Arthur Germano Fett-Neto; Renata Vidor Contri; Patrícia da Silva Malheiros (Food Research International, 2023)

Use of a product based on wood vinegar of Eucalyptus clone I144 used in the control of bovine mastitis - Bismark Alves da Silva; Francisco Marlon Carneiro Feijó; Nilza Dutra Alves; Alexandre Santos Pimenta; Leon Denner Moreira Benicio; Enilson Claudio da Silva Júnior; Caio Sérgio Santos; Alexsandra Fernandes Pereira; Yasmin Beatriz França Moura; Gil Sander Prospero Gama; Evilasio de Souza Lima Neto (Veterinary Microbiology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Effect of diets containing commercial bioactive compounds on Salmonella Heidelberg infection in broiler chicks - Victória Veiga Alves; Letícia Cury Rocha Veloso Arantes; Alexandre Lemos de Barros Moreira Filho; Mailson da Silva Teixeira; Eudes Fernando Alves da Silva; Mauro de Mesquita Souza Saraiva; Ricardo Barbosa de Lucena; Patrícia Emília Naves Givisiez; Celso José Bruno de Oliveira; Oliveiro Caetano de Freitas Neto (Brazilian Journal of Microbiology, 2023)

Renewable processes of synthesis of biolubricants catalyzed by lipases - Isamayra Germano de Sousa; Gabrielly Ferreira Mota; Antônio Luthierre Gama Cavalcante; Thales Guimarães Rocha; Patrick da Silva Sousa; Jeferson Yves Nunes Holanda Alexandre; José Erick da Silva Souza; Francisco Simão Neto; Francisco Thálysson Tavares Cavalcante; Ada Amélia Sanders Lopes; José C.S. dos Santos (Journal of Environmental Chemical Engineering, 2023)

FK506 impairs neutrophil migration that results in increased polymicrobial sepsis susceptibility - Vanessa de Fátima Borges; Leticia Selinger Galant; Alexandre Kanashiro; Fernanda Vargas e Silva Castanheira; Valter Vinícius Silva Monteiro; Diego Ângelo Duarte; Filipe Camargo Rodrigues; Camila Meirelles de Souza Silva; Ayda Henriques Schneider; Guilherme Cesar Martelossi Cebinelli; Mikhael Haruo Fernandes de Lima; João Paulo de Biaso Viola; et al. (Inflammation Research, 2023)

The use of mulch in cultivating the forage cactus optimizes yield in less time and increases the water use efficiency of the crop - Hygor Kristoph Muniz Nunes Alves; Thieres George Freire da Silva; Alexandre Maniçoba da Rosa Ferraz Jardim; Luciana Sandra Bastos de Souza; George do Nascimento Araújo Júnior; Carlos André Alves de Souza; Magna Soelma Beserra de Moura; Gherman Garcia Leal de Araújo; Fleming Sena Campos; José Francisco da Cruz Neto (Irrigation and Drainage, 2023)
Measurements of crop evapotranspiration (ET C ) and crop coefficients ( k C ) in cactus have not yet been adjusted for the phenological stage using conservation practices (i.e. mulching). In this study, soil water dynamics, ET C and k C were measured in the forage cactus under cultivation systems with (WM) and without (NM) the use of mulch in the semi‐arid region of Brazil. Opuntia stricta was subjected to irrigation depths based on a percentage of the reference evapotranspiration (ET 0 ) (rainfed, 25, 50, 75 and 100%) and to two systems of cultivation: WM and NM. Over time, the phenophases ( φ Ph) were established; the soil water balance components were calculated and the crop yield was evaluated at harvest. The use of 8.2 Mg ha −1 mulch led to almost no reduced water consumption by the crop when compared to the NM system; however, the mulch did maximize yield, at 839°C day, when irrigated with 50% ET 0 . The k C value was higher under the WM system, with the differences decreasing throughout the cycle ( φ PhI, 36%; φ PhII, 27%; φ PhIII, 23%; φ PhIV‐HT, 17%; and φ PhIV‐RF, 14%). Therefore, the use of mulch in cultivating the cactus optimized forage production in less time and significantly increased the water use efficiency of the crop.

Numerical Simulation of Embankment Construction on Soft Soil: A Case - Andréa Batista de Farias Dias; Thiago Augusto da Silva; Igor Fernandes Gomes; Silvio Romero de Melo Ferreira; Alexandre Duarte Gusmão; Jean Baptiste Joseph; Manoel Porfirio Cordão Neto (Geotechnical and Geological Engineering, 2022)

Long‐term unsustainable patterns of development rather than recent deforestation caused the emergence of Orthocoronavirinae species - Sérvio P. Ribeiro; Debmalya Barh; Bruno Silva Andrade; Raner José Santana Silva; Diogo Henrique Costa‐Rezende; Paula Luize Camargos Fonseca; Sandeep Tiwari; Marta Giovanetti; Luiz Carlos Junior Alcantara; Vasco Ariston Azevedo; Preetam Ghosh; José Alexandre F. Diniz‐Filho; et al. (Environmental Microbiology, 2022)
We investigated whether a set of phylogeographical tracked emergent events of Orthocoronavirinae were related to developed, urban and polluted environments worldwide. We explored coronavirus records in response to climate (rainfall parameters), population density, CO 2 emission, Human Developmental Index (HDI) and deforestation. We contrasted environmental characteristics from regions with spillovers or encounters of wild Orthocoronavirinae against adjacent areas having best‐preserved conditions. We used all complete sequenced CoVs genomes deposited in NCBI and GISAID databases until January 2021. Except for Deltacoronavirus, concentrated in Hong Kong and in birds, the other three genera were scattered all over the planet, beyond the original distribution of the subfamily, and found in humans, mammals, fishes and birds, wild or domestic. Spillovers and presence in wild animals were only reported in developed/densely populated places. We found significantly more occurrences reported in places with higher HDI, CO 2 emission, or population density, along with more rainfall and more accentuated seasonality. Orthocoronavirinae occurred in areas with significantly higher human populations, CO 2 emissions and deforestation rates than in adjacent locations. Intermediately disturbed ecosystems seemed more vulnerable for Orthocoronavirinae emergence than forested regions in frontiers of deforestation. Sadly, people experiencing poverty in an intensely consumerist society are the most vulnerable.

Wound healing activity of lectin isolated from seeds of Centrolobium microchaete Mart. ex Benth. on cutaneous wounds in mice - Luiz Gonzaga do Nascimento Neto; Mayron Alves de Vasconcelos; Aryane de Azevedo Pinheiro; Ana Patrícia Magalhães Ramos; Renally Barbosa da Silva; Alexandre Lopes Andrade; Francisco Vassiliepe Sousa Arruda; José Ajax Nogueira Queiroz; Edson Holanda Teixeira (Natural Product Research, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Nutritive value of Urochloa decumbens Stapf R. D. Webster and Mimosa caesalpiniifolia Benth. and performance of cattle in monoculture and silvopastoral systems, in the Agreste region of Pernambuco - Chrislanne Barreira de Macêdo Carvalho; Alexandre Carneiro Leão de Mello; Márcio Vieira da Cunha; Valéria Xavier de Oliveira Apolinário; José Carlos Batista Dubeux Júnior; Diana Valadares Pessoa; Pedro Mouzinho de Oliveira Neto; Vanilson Pedro da Silva (Tropical Animal Health and Production, 2022)

Flaxseed added to the diet of Alpine goats affects the nutrients intake and blood parameters - Patrícia Alves Dutra; Luis Fernando Batista Pinto; Bianor Matias Cardoso-Neto; Claudineia Silva Mendes; Alexandre Moraes Pinheiro; Larissa Pires Barbosa; Taiala Cristina de Jesus Pereira; Gleidson Giordano Pinto de Carvalho (Tropical Animal Health and Production, 2022)

Genomic analyses of a novel bioemulsifier-producing Psychrobacillus strain isolated from soil of King George Island, Antarctica - Mariana Barbalho Farias da Silva; Fabio Faria da Mota; Diogo Jurelevicius; Vasco Ariston de Carvalho Azevedo; Mateus Matiuzzi da Costa; Aristóteles Góes-Neto; Rommel Thiago Jucá Ramos; Siomar de Castro Soares; Alexandre Soares Rosado; Lucy Seldin (Polar Biology, 2022)

SIA‐BRA: A database of animal stable carbon and nitrogen isotope ratios of Brazil - Thaís Rovere Diniz‐Reis; Fernanda Gaudio Augusto; Adibe Luiz Abdalla Filho; Maria Gabriella da Silva Araújo; Siglea Sanna Freitas Chaves; Rodrigo Figueiredo Almeida; Elen Blanco Perez; Carla da Penha Simon; Janaína Leite de Souza; Cristiane Formigosa Gadelha da Costa; Taciana Figueiredo Gomes; Melissa Gaste Martinez; et al. (Global Ecology and Biogeography, 2022)
Motivation SIA‐BRA is a data set that compiles stable carbon (C) and nitrogen (N) isotope ratios of terrestrial and aquatic animals sampled in Brazilian biomes and coastal marine areas. Stable isotope ratios are helpful in animal ecology for several reasons; for instance, they can be used to investigate trophic niches, energy sources (diet tracing) and to track migration patterns. The Neotropics are considered one of the most undersampled regions of the world. Given that Brazil is a continental country where most of the dietary ecology of animal species is under‐assessed, we believe that the SIA‐BRA can provide important complementary information to address this gap in the literature. Additionally, the SIA‐BRA data set allows future investigations to address many questions concerning diet tracing, habitat use, food webs, foraging ecology, physiological aspects and effects of phylogeny on dietary ecology. Main type of variable investigated Carbon and nitrogen stable isotope ratios for terrestrial and aquatic animals. Spatial location and grain The SIA‐BRA included animal tissues sampled in 964 sites in the main Brazilian biomes and coastal marine areas. Time period The data represent information published and/or sampled from 1984 to 2021. Major taxa studied and measurement level The SIA‐BRA contains isotopic data of c . 21,804 non‐captive wildlife specimens, excluding livestock production or laboratory experiments. They were 13,881 vertebrates and 7,923 invertebrates. They were divided into the following habitats: terrestrial (30% of the total), freshwater (27%), oceanic (40%) and estuarine (4%). There were 11 phyla, with a clear dominance of Chordata (64%) and Arthropoda (29%), 36 classes, 154 orders, 473 families, 894 genera and 1,157 species. Software format Data are supplied as a comma‐delimited text file (.csv).

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Evaluation of cytotoxic, immunomodulatory effects, antimicrobial activities and phytochemical constituents from various extracts of Passiflora edulis F. flavicarpa (Passifloraceae) - Georon Ferreira de Sousa; Dayane Kelly Dias do Nascimento Santos; Ricardo Sérgio da Silva; Bárbara Rafaela da Silva Barros; Iranildo José da Cruz-Filho; Bárbara de Azevedo Ramos; Túlio Diego da Silva; Pérsio Alexandre da Silva; Reginaldo Gonçalves de Lima-Neto; Norma Buarque de Gusmão; Marcia Silva do Nascimento; Cristiane Moutinho Lagos de Melo (Natural Product Research, 2021)

Hypotensive activity of Campomanesia xanthocarpa leaf extract: beyond angiotensin II type 1 receptor blockage - Ingrid Beatriz de Melo Morais; Denise Brentan Silva; Carlos Alexandre Carollo; Marcos Luiz Ferreira-Neto; Patrícia Fidelis-de-Oliveira; Luiz Borges Bispo-da-Silva (Natural Product Research, 2021)

Improved cotton transformation protocol mediated by Agrobacterium and biolistic combined-methods - Thuanne Pires Ribeiro; Isabela Tristan Lourenço-Tessutti; Bruno Paes de Melo; Carolina Vianna Morgante; Alvaro Salles Filho; Camila Barrozo Jesus Lins; Gilanna Falcão Ferreira; Glênia Nunes Mello; Leonardo Lima Pepino Macedo; Wagner Alexandre Lucena; Maria Cristina Mattar Silva; Osmundo Brilhante Oliveira-Neto; et al. (Planta, 2021)

Detection and application of novel SSR markers from transcriptome data for Astronium fraxinifolium Schott, a threatened Brazilian tree species - Maiara R. Cornacini; Ricardo O. Manoel; Marcelo A. M. Alcantara; Mário L. T. Moraes; Edvaldo A. A. Silva; Leonel G. Pereira Neto; Alexandre M. Sebbenn; Bruno C. Rossini; Celso L. Marino (Molecular Biology Reports, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Bacillus thuringiensis endotoxin production: a systematic review of the past 10 years - José Manoel W. Duarte Neto; Maria Carolina de A. Wanderley; Túlio Alexandre F. da Silva; Daniela A. Viana Marques; Gilvanda R. da Silva; Josimar Fernandes Gurgel; José de Paula Oliveira; Ana Lúcia F. Porto (World Journal of Microbiology and Biotechnology, 2020)

Antimicrobial activity and antibiotic synergy of a biphosphinic ruthenium complex against clinically relevant bacteria - Alexandre Lopes Andrade; Mayron Alves de Vasconcelos; Francisco Vassiliepe de Sousa Arruda; Luiz Gonzaga do Nascimento Neto; José Marcos da Silveira Carvalho; Ana Claudia Silva Gondim; Luiz Gonzaga de França Lopes; Eduardo Henrique Silva Sousa; Edson Holanda Teixeira (Biofouling, 2020)

Concentration of Traces Metals in Underground Dams in the Semi-Arid of the Rio Grande do Norte State, Brazil: Case Study of the Sub-Basin of the Cobras River - Alexandre de Oliveira Lima; Nildo da Silva Dias; Cleyton dos Santos Fernandes; Francisco Pinheiro Lima Filho; Rene Chipana Rivera; Yago Leopoldo Eleuterio Gurgel de Sousa; Líssia Letícia de Paiva Oliveira; José Darcio Abrantes Sarmento; Hozano de Souza Lemos Neto (Water, Air, & Soil Pollution, 2020)

Quantitative analysis of black blotching in a crossbred red tilapia and its effects on performance traits via a path analysis methodology - Aline de Assis Lago; Rafael Vilhena Reis-Neto; Tiago Teruel Rezende; Mayra Cristina da Silva Ribeiro; Rilke Tadeu Fonseca de Freitas; Alexandre Wagner Silva Hilsdorf (Journal of Applied Genetics, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Brown eye spot in coffee subjected to different drip irrigation and fertilization management - Mauro Peraro Barbosa Junior; Edson Ampélio Pozza; Helon Santos Neto; Mirian de Lourdes Oliveira e Silva; Adélia Aziz Alexandre Pozza; Rubens José Guimarães; Paulo Estevão de Souza (Australasian Plant Pathology, 2019)

Spatio-temporal aspects of brown eye spot and nutrients in irrigated coffee - Marília Goulart da Silva; Edson Ampélio Pozza; Eugênio Chaves; Helon Santos Neto; Gabriel Brandão Vasco; Paulo Victor Augusto Azevedo de Paula; Gabriel Avelar Dornelas; Marcelo de Carvalho Alves; Mirian de Lourdes Oliveira e Silva; Adélia Aziz Alexandre Pozza (European Journal of Plant Pathology, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

REM sleep behavior disorder in patients with Parkinson’s disease: clinical and polysomnographic characteristics - Manoel Alves Sobreira-Neto; Márcio Alexandre Pena-Pereira; Emmanuelle Silva Tavares Sobreira; Marcos Hortes Nisihara Chagas; Carlos Maurício Oliveira de Almeida; Regina Maria França Fernandes; Vitor Tumas; Alan Luiz Eckeli (Sleep and Biological Rhythms, 2019)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Intake and ingestive behavior of lambs fed diets containing ammoniated buffel grass hay - Alexandre Fernandes Perazzo; Sansão de Paula Homem Neto; Ossival Lolato Ribeiro; Edson Mauro Santos; Gleidson Giordano Pinto de Carvalho; Juliana Silva de Oliveira; Higor Fábio Carvalho Bezerra; Fleming Sena Campos; José Esler de Freitas Junior (Tropical Animal Health and Production, 2017)

Anti-inflammatory and anti-arthritic activities of 3,4-dihydro-2,2-dimethyl-2H-naphthol[1,2-b]pyran-5,6-dione (β-lapachone) - Marília Maria Sitônio; Carlson H. R. de Carvalho Júnior; Ingrid de A. Campos; José Bruno Nunes Ferreira Silva; Maria do Carmo Alves de Lima; Alexandre J. S. Góes; Maria Bernadete Sousa Maia; Pedro J. Rolim Neto; Teresinha G. Silva (Inflammation Research, 2013)

A geographical genetics framework for inferring homing reproductive behavior in fishes - Mariana Pires de Campos Telles; Rosane Garcia Collevatti; Marcio Candido da Costa; Ronaldo Borges Barthem; Nelson Jorge da Silva; Advaldo Carlos Souza Neto; José Alexandre Felizola Diniz-Filho (Genetica, 2011)